Islamic Education Comprehension among Engineering Students:Effects of Attitude and Motivation to Learn as an Antecedent Mediator - Rinaldi; Primandari, Sri Rizki Putri; Wahyuni, Deni; Hamzah, Mohd Isa; Alimin, Masnaini (Al-Hayat: Journal of Islamic Education, 2024)
This study aimed to analyse the effect of attitudes and motivation to learn on Islamic education comprehension among engineering students. It also identified the role of motivation as a mediator between attitude and Islamic education comprehension. This study employed a quantitative method with a survey study. The participants were first-year and end-year engineering students in Higher Education Institutions who were chosen by purposive sampling. Data were gathered from 250 samples by using one set of questionnaires. SmartPLS with Structure Equation Modeling was carried out to analyse data. Furthermore, path analysis at two-tailed significance (p<0.05) examines hypotheses and the effect of each antecedent on Islamic education comprehension. The findings of this study confirmed that attitude had no significant impact on Islamic education comprehension among engineering students. But attitude affects the motivation to learn. Motivation to learn affects Islamic education comprehension. These findings reveal that motivation to learn is a significant antecedent as a mediator in the relationship between attitude and Islamic education comprehension. This study is limited by a questionnaire to gather the data and area restrictions. This study involved Muslim engineering students in higher education institutions who have not been assigned to other studies on Islamic education. Generally, other Islamic education studies analyse subjects in Madrasah or other Islamic education institutions.